Molecular evidence of field cancerization initiated by diabetes in colon cancer patients. Issue 4 (16th February 2019) - Del Puerto‐Nevado, Laura; Minguez, Pablo; Corton, Marta; Solanes‐Casado, Sonia; Prieto, Isabel; Mas, Sebastian; Sanz, Ana Belen; Gonzalez‐Alonso, Paula; Villaverde, Cristina; Portal‐Nuñez, Sergio; Aguilera, Oscar; Gomez‐Guerrero, Carmen; et al.
Abstract : The potential involvement of type 2 diabetes mellitus (T2DM) as a risk factor for colon cancer (CC) has been previously reported. While several clinical studies show a higher incidence of CC and a lower survival rate in diabetics, others report no association. Our own experience indicates that diabetes does not seem to worsen the prognosis once the tumor is present. Despite this controversy, there are no wide‐spectrum molecular studies that delve into the impact of T2DM‐related mechanisms in colon carcinogenesis. Here, we present a transcriptomic and proteomic profiling of paired tumor and normal colon mucosa samples in a cohort of 42 CC patients, 23 of which have T2DM. We used gene set enrichment and network approaches to extract relevant pathways in diabetics, referenced them to current knowledge, and tested them using in vitro techniques. Through our transcriptomics approach, we identified an unexpected overlap of pathways overrepresented in diabetics compared to nondiabetics, in both tumor and normal mucosa, including diabetes‐related metabolic and signaling processes. Proteomic approaches highlighted several cancer‐related signaling routes in diabetics found only in normal mucosa, not in tumors. An integration of the transcriptome and proteome analyses suggested the deregulation of key pathways related to colon carcinogenesis which converged on tumor initiation axis TEAD/YAP‐TAZ as a potential initiator of the process. In vitro studies confirmed upregulation of this pathway in nontumor colon cells under high‐glucose conditions. In conclusion, T2DM associates with deregulation of cancer‐related processes in normal colon mucosa adjacent to tissue which has undergone a malignant transformation. These data support that in diabetic patients, the local microenvironment in normal colon mucosa may be a factor driving field cancerization promoting carcinogenesis. Our results set a new framework to study links between diabetes and colon cancer, including a new role of the TEAD/YAP‐TAZ complex as a potential driver. Abstract : We present here for the first time molecular evidence of the impact of type 2 diabetes mellitus driving field cancerization in colon cancer. We integrated transcriptomic and proteomic screening of tumor and normal colon mucosa samples and thereby identified key pathways activated by diabetes related to carcinogenesis which converged on tumor initiation axis TEAD/YAP‐TAZ as a potential initiator of the process.